Computer simulation study of apatite mineral surfaces and interfaces with silicates - Mkhonto, Donald (University of Limpopo (Turfloop Campus), 2005)
We have derived a potential model for °uorapatite Ca10(PO4)6F2, ¯tted to structure, elastic constants and vibrational frequencies of the phosphate groups, which is compatible with existing calcite and °uorite potential mod- els. We then modelled the structure and stabilities of the dry and hydrated f0 0 0 1g, f1 0 1 0g, f1 0 1 1g, f1 1 2 0g, f1 0 1 3g and f1 1 2 1g surfaces, which calculations con¯rmed the experimental dominance of the f0 0 0 1g surface, which is prominently expressed in the calculated thermodynamic morphologies. The dehydrated morphology further shows the experimental f1 1 2 1g twinning plane, while the f1 0 1 0g cleavage plane is expressed in the hydrated morphology. Molecular adsorption of water has a stabilising e®ect on all six surfaces, where the surfaces generally show Langmuir be- haviour and the calculated hydration energies indicate physisorption (73 - 88 kJ mol¡1). The chains of °uoride ions surrounded by hexagonal calcium channels can become distorted in two major ways during relaxation: either by a shortening/lengthening of the FF distances, when the channel is perpendicular to the surface, or by distortion of the CaF bonds when the channel is parallel to the surface. Both distortions occur when the channel runs at an angle to the surface. Other relaxations include compression of the calcium sub-lattice and rotation of surface phosphate groups. We have modelled adsorption of a range of organic molecules onto dif- ferent °uorapatite surfaces, due to the importance of organic/ inorganic in- teractions in biological situations. We have selected organic molecules that represent a model for the carboxylic acids, alkyl hydroxamates and those 3 that contain both the aldehyde and hydroxyl functional groups. Adhesion of these organic molecules on the surfaces has shown strong interaction between the surface's Ca ions and the molecule's oxygens, more especially the car- bonyl oxygens than any other interactions. It was found that the number of interactions between the ions of adsorbate molecule and the mineral surfaces thus contribute signi¯cantly to the exothemicity of adsorption. Further more, simulations of apatite thin ¯lms at a range of ®-quartz surfaces have shown how the strength of adhesion between thin ¯lms of ap- atite material and ceramic silica surfaces is crucially dependent upon both the orientation of the ¯lm relative to the substrate and the nature of the silica surfaces, a ¯nding that is important in a wide number of applications, from basic geological research on intergrowth of phosphate and silicate rock minerals to the search for more e®ective surgical implant materials. It was shown that although the unrelaxed quartz surface is more reactive toward the apatite ¯lm, the more regular thin ¯lm structures grown at the pre-relaxed quartz surfaces lead to more stable interfaces. Film growth at the unrelaxed quartz surface is energetically increasingly unfavorable, whereas growth at the pre-relaxed surface is calculated to continue beyond the ¯rst layer, where the adhesion energy is convergent with the layer growth of the thin ¯lm. Ad- hesion of apatite thin ¯lm on hydroxylated surfaces of ®-quartz has shown to be energetically less favourable than at dry surfaces. This was because the thin ¯lm interact mainly with the hydroxyl ions on the surface of quartz. However, the adhesion energy is still convergent with layer growth of the thin ¯lm on the hydroxylated surfaces.
Thesis (Ph.D (Physics)) --University of Limpopo, 2005
Keywords: Computer simulations; Apatite mineral surfaces; Silicates; 549.6; Mineralogy; Silicates minerals -- South Africa